Student Perception towards Outdoor Learning for Descriptive Text Material: A Case Study at SMPN 1 Krian - Putri, Faradhillah Ananda; Rakhmawati; Septianisari, Ima (ICONELT, 2024)
This research discussed a case study exploring student perception toward outdoor learning, especially in learning descriptive text at SMPN 1 Krian. Using qualitative research, this research interviewed six students at SMPN 1 Krian to gather data on their perception of experiencing outdoor learning for descriptive text. The result of this research indicates that through outdoor learning, students are able to learn and write descriptive text by direct observation of real objects that are being described. Furthermore, findings show that students engaged in motivation when learning outdoors instead of inside the classroom. This research concludes that outdoor learning not only facilitates students in learning and writing descriptive texts but also boosts student’s motivation to learn.